Association between quality and duration of sleep and subjective cognitive decline: a cross-sectional study in South Korea - Hye Jin Joo (Nature Portfolio, 2021)
Abstract Sleep is being emphasized as a factor that improves mental health and quality of life. Here, we aimed to investigate the association between the quality and duration of sleep and subjective cognitive decline in the Korean population. We used the 2018 Korean Community Health Survey data that are nationwide representative data collected by the Korea Centers for Disease Control and Prevention. Sleep quality was measured using the Korean version of Pittsburgh Sleep Quality Index. The study population comprised 206,719 individuals aged 19 years and over. We used multiple logistic regression for the analysis. Individuals of both sexes with poor sleep quality were more likely to experience subjective cognitive decline compared with the reference group (good sleep quality) (men, odds ratio (OR) = 1.97 [95% confidence interval (CI) 1.86–2.09]; women, OR = 1.75 [95% CI 1.67–1.84]). U-shape associations were found between sleep duration and subjective cognitive decline. Additionally, the presence of depressive symptom or stress and health-related behaviors, including smoking, drinking, and not walking, were high-risk factors for subjective cognitive decline. Our results indicate that poor sleep quality might contribute to subjective cognitive decline in the Korean population. We suggest the implementation of intervention measures for poor sleep behaviors to prevent cognitive decline.